A Fanci knockout mouse model reveals common and distinct functions for FANCI and FANCD2. Issue 14 (20th June 2019) - Dubois, Emilie L; Guitton-Sert, Laure; Béliveau, Mariline; Parmar, Kalindi; Chagraoui, Jalila; Vignard, Julien; Pauty, Joris; Caron, Marie-Christine; Coulombe, Yan; Buisson, Rémi; Jacquet, Karine; Gamblin, Clémence; et al.
Abstract: Fanconi Anemia (FA) clinical phenotypes are heterogenous and rely on a mutation in one of the 22 FANC genes ( FANCA-W)  involved in a common interstrand DNA crosslink-repair pathway. A critical step in the activation of FA pathway is the monoubiquitination of FANCD2 and its binding partner FANCI. To better address the clinical phenotype associated with FANCI and the epistatic relationship with FANCD2, we created the first conditional inactivation model for FANCI in mouse. Fanci   −/−  mice displayed typical FA features such as delayed development in utero, microphtalmia, cellular sensitivity to mitomycin C, occasional limb abnormalities and hematological deficiencies. Interestingly, the deletion of Fanci leads to a strong meiotic phenotype and severe hypogonadism. FANCI was localized in spermatocytes and spermatids and in the nucleus of oocytes. Both FANCI and FANCD2 proteins co-localized with RPA along meiotic chromosomes, albeit at different levels. Consistent with a role in meiotic recombination, FANCI interacted with RAD51 and stimulated D-loop formation, unlike FANCD2. The double knockout Fanci −/− Fancd2 −/− also showed epistatic relationship for hematological defects while being not epistatic with respect to generating viable mice in crosses of double heterozygotes. Collectively, this study highlights common and distinct functions of FANCI and FANCD2 during mouse development, meiotic recombination and hematopoiesis.